Pengaruh Model Pembelajaran Generatif Berbasis Lingkungan Terhadap Kompetensi Pengetahuan IPA - Ekasari, Ni Luh Putu; Smara Putra, DB.Kt.Ngr.; Surya Abadi, I.B.G. (Jurnal Ilmiah Sekolah Dasar, 2018)
The perpose of to research that there was a significant effect of generative environment-based learning model on science knowledge competence in fourth grade students of SD Gugus I Gusti Ngurah Rai Denpasar Academic Year 2017/2018. The type of this research was quantitative research with nonequivalent control group design. The population of this research was all fourth graders of SD Gugus I Gusti Ngurah Rai which amounts to 249 people. The sample was done by random sampling technique. The sample in this research were the students of grade IVC SDN 4 Sanur with the number of 33 students as experiment group and students of grade IV SDN 11 Sanur with 32 students as control group. The data collected by using the test method in the form of a standard multiple-choice objective test. The data obtained analyzed using the t-test. Based on the result of data analysis gain score normalized obtained thitung = 3,507 while at significance level 5% and dk = 63 obtain ttabel value = 2,000 so thitung = 3.507> ttabel = 2,000. Based on the test criteria, Ho is reject and Ha accept. The average score of science knowledge competence in the group that is though by the generative model base on the environment is 51.84, while in the group taught by conventional learning is 33.78. Based on these results it can be concluded that there is influence of environment-based generative learning model to science knowledge competence of student of IV grade SD Gugus I Gusti Ngurah Rai Denpasar academic year 2017/2018